The counterfeit goods conundrum: an analysis of demand situation among Malaysian consumers / Teo Carol Boon Chui and Mohd Zahin Mohd Yusof - Teo, Carol Boon Chui; Mohd Yusof, Mohd Zahin (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2017)
This paper examines the tricky and confusing problem of counterfeit goods demand. Counterfeit activities are getting more rampant, sophisticated and aggressive on a worldwide basis. Malaysia remains an ideal transit hub for counterfeit goods and regarded as lack in placing a premium on intellectual property rights. There is a need to address this conundrum of consumers who are fully aware of this illegal trade but continue to patronize. Measures undertaken by government dealt mainly with supply side of counterfeit goods but there is lack of effort on demand side control. An analysis into consumer attitude towards demand for counterfeit goods focusing on factors influencing purchase is warranted. This study utilized the integrated model of counterfeit goods purchase by Matos et al. (2007). Methodology entailed survey approach on 150 users at a locality in Kuala Lumpur. Findings showed positive and significant relationships between perceived risk, integrity and status as predictors of consumer attitude towards counterfeit goods. Findings provided implications for anti-counterfeit measures to go beyond awareness, communication and information on risks but more on emotional closeness to the consumer. Changing mindsets is necessary making clear to consumers that counterfeit purchase is stealing. Companies can be proactive by revealing the depth and breadth of counterfeiting and creating public consciousness.